PENERAPAN LANGKAH POLYA DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS IV PADA MATERI BANGUN RUANG - Nur Ainsah Saleh; Fida Rahmantika Hadi; Titik Isdarwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The research aims to examine whether the application of Polya's steps improves the learning outcomes of class IV students at SDN 01 Taman Kota Madiun on building materials. This research uses a type of action with the type of data used being quantitative and qualitative descriptive. Quantitative data is data regarding learning outcomes obtained through learning results tests, while qualitative data is data regarding student learning activities obtained through observation. The subjects in this research were 24 Class IV-A students at SDN 01 Taman Kota Madiun in the 2023/2024 academic year. The results of the research showed that in cycle I, only 10 students, or 41.67% completed individually and the average score was 61.25, while in cycle II 17 students, or 71% had completed the completion and average score. obtained was 73.79. Based on the results of this research, it was concluded that the application of a problem-solving approach in learning mathematics regarding building materials on cubes and blocks was proven to be able to improve student learning outcomes in class IV at SDN 01 Taman Kota Madiun